Multiple variants aggregate in the neuregulin signaling pathway in a subset of schizophrenia patients - Hatzimanolis, A (Nature Publishing Group, 2013)
Despite the strongly held view that schizophrenia (SZ) shows substantial genetic heterogeneity, pathway heterogeneity, as seen in cancer where different pathways are affected in similar tumors, has not been explored. We explore this possibility in a case-only study of the neuregulin signaling pathway (NSP), which has been prominently implicated in SZ and for which there is detailed knowledge on the ligand- and receptor-processing steps through β- and γ-secretase cleavage. We hypothesize that more than one damaging variants in the NSP genes might be necessary to cause disease, leading to an apparent clustering of such variants in only the few patients with affected NSP. We analyze linkage and next-generation sequencing results for the genes encoding components of the pathway, including NRG1, NRG3, ERBB4, β-secretase and the γ-secretase complex. We find multiple independent examples of supporting evidence for this hypothesis: (i) increased linkage scores over NSP genes, (ii) multiple positive interlocus correlations of linkage scores across families suggesting each family is linked to either many or none of the genes, (iii) aggregation of predicted damaging variants in a subset of individuals and (iv) significant phenotypic differences of the subset of patients carrying such variants. Collectively, our data strongly support the hypothesis that the NSP is affected by multiple damaging variants in a subset of phenotypically distinct patients. On the basis of this, we propose a general model of pathway heterogeneity in SZ, which, in part, may explain its phenotypic variability and genetic complexity.